Evaluasi Kebijakan Insentif Energi untuk Mendorong Inovasi Teknologi Migas Bersih - Lia Nurmeiliani (Asian Journal of Multidisciplinary Research, 2025)
This study addresses the problem of whether energy incentive policies effectively encourage the adoption of clean oil and gas technologies through innovation and diffusion within the sector. The objective is to evaluate how the policy instrument design and implementation relate to clean technology innovation and the resulting technology adoption outcomes. Using a qualitative library-research approach, the study synthesizes primary and secondary literature relevant to Energy Incentive Policy, Clean Oil and Gas Technology Innovation, and Technology Adoption. Data are collected through systematic review of books, journal articles, policy-related reports, and prior studies, followed by content analysis to identify patterns and thematic linkages across the reviewed materials. The study concludes that policy effectiveness depends on the alignment between incentive mechanisms and the practical determinants of technology adoption, and that well-targeted incentives are necessary to reduce barriers to innovation in clean oil and gas operations.